Seroprevalence and risk behaviors of bovine brucellosis in the south-western prefecture of Haho, Togo, January to April 2020. (March 2022) - Logonda, P.; Otshudiandjeka, J.; Pato, P.
Abstract : Purpose: Brucellosis is a public health problem; it is included on the list of priority animal diseases under epidemiological surveillance in Togo but we the lack of information on the disease for the study area. The objective of the study was to determine the seroprevalence and risk behaviors of brucellosis in dairy cattle farms in the southwest of Haho prefecture in Togo from January to April 2020. Methods & Materials: We conducted a cross-sectional study from January 1 to April 31, 2020. Blood samples were taken from lactating cows using the Rose Bengal test and a questionnaire was administered to breeders. Results: In total, 52 samples were taken from the cattle and 52 breeders surveyed. We obtained a prevalence of 13.46% in cattle. The risk behaviors identified were: lack of knowledge about Brucellosis, handling of abortions; placentas and cattle without gloves, the consumption of raw milk and cheese, the abandonment of runts in fields which are sometimes eaten, and the failure to isolate the cattle during births or abortions. Conclusion: Brucellosis exists in dairy cattle farms in the prefecture of Haho in Togo, and the risk of contamination of breeders is high. We therefore recommend that breeders: wear gloves when handling abortions, placentas and animals, then pasteurize the milk before consumption.